Kondisi Sanitasi Dalam Meningkatkan Kualitas Kesehatan Narapidana di Lembaga Pemasyarakatan - Aldy Dwi Aryanto; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Sanitation is something that is often related to humans and their environment. Parts of sanitation include the cleanliness of a place, clean water treatment, rubbish disposal systems and waste disposal systems. Sanitation is needed in all places, including correctional institutions. The health of prisoners can be disturbed if sanitation in the correctional institution does not work well. Many inmates contract skin diseases such as scabies, ARI, and diarrhea as a result of poor sanitation systems in correctional institutions. Therefore, this research was conducted to determine the sanitary conditions in correctional institutions to improve the quality of prisoners' health. The research method used is descriptive qualitative and data collection using the observation method. The conclusion from the results of this research is that the sanitation system in correctional institutions is running well. However, there is a need to repair and upgrade facilities to improve sanitation in correctional institutions. The correctional institution must also be able to routinely control and clean the environment around the correctional institution so that it does not cause diseases that could harm the prisoners inside.